The Role of IL-17 in the Association between Pneumococcal Pneumonia and Allergic Sensitization - Hongxia Zhao; Cheol-In Kang; Mark S. Rouse; Robin Patel; Hirohito Kita; Young J. Juhn (International Journal of Microbiology)
Interleukin- (IL-) 17 is important in the development of asthma and host defense against pneumococci. We determined the role of IL-17 in the risk of pneumococcal pneumonia. We challenged mice intranasally with a bioluminescent Streptococcus pneumoniae strain after sensitization and challenge with ovalbumin (OVA). We measured the levels of cytokines, including IL-17 (pg/mL), in the lung homogenate in experimental mice with and without OVA sensitization/challenge, as well as those with and without pneumococcal pneumonia. IL-17 levels were significantly lower in OVA-sensitized/challenged mice (9.69 ± 1.49), compared to the control mice (20.92 ± 1.82, P < 0.001). In our overall analysis, including IL-4 and IL-17 levels and OVA sensitization/challenge, IL-4 levels (OR: 81.9, 95%CI: 4.3–1523 per increment of 1.0 pg/mL, P = 0.003) were more significant than IL-17 levels (OR: 1.1, 95%CI: 1.03–1.17 per increment of 1.0 pg/mL, P = 0.003) in determining the risk of pneumococcal pneumonia. IL-17 levels result in a much smaller impact on the risk for pneumococcal pneumonia, compared to IL-4 levels.